Reflecting on vocation: a randomized trial of online expressive writing career interventions - White, Micah, author; Dik, Bryan, advisor; Becker, Tony, committee member; Beseler, Cheryl, committee member; Peila-Shuster, Jackie, committee member (Colorado State University. Libraries, 2020)
Though recent research on calling has connected the construct to a variety of positive career-related and general well-being outcomes, there remains a scarcity of empirically tested interventions to increase calling. The present study sought to address this gap in the literature by experimentally testing three writing interventions based on Pennebaker's expressive writing paradigm (Pennebaker & Beall, 1986) with the intention of increasing participants' sense of calling and other career-related outcomes. These interventions included articulating one's general career goals (i.e., the career goals condition), anticipating potential future career obstacles (i.e., the adaptability condition), and reflecting on one's life purpose as it relates to one's future career (i.e., the purpose condition). This study also used text analysis software to explore whether the linguistic content of participant journal entries was predictive of study outcomes. While many results were non-significant, participants in the purpose condition reported greater presence of calling and vocational identity at post-intervention than participants in other conditions. Furthermore, use of causation words was predictive of presence of calling and career adaptability while use of negative emotion words was predictive of career confidence. Results appeared to support previous career development theory that has suggested that narrative-based reflections on one's personal passions, motivations, and purpose, as well as the prosocial impact of one's career, are beneficial. Limitations and considerations of how to improve these interventions in future studies are also discussed.